Erectile Dysfunction and Target Organ Damage in the Early Stages of Hypertension. Issue 9 (11th July 2013) - Kakkavas, Apostolos; Tsioufis, Costas; Tsiachris, Dimitris; Thomopoulos, Costas; Dimitriadis, Kyriakos; Milkas, Anastasios; Alexopoulos, Dimitrios; Kallikazaros, Ioannis; Stefanadis, Christodoulos
Abstract : The authors investigated whether erectile dysfunction (ED) in the early stages of hypertension is associated with heightened end‐organ damage. A total of 174 consecutive men with untreated, newly diagnosed essential hypertension (aged 50.3 years, office blood pressure [BP] 150/98 mm Hg) were studied. All participants underwent 24‐hour ambulatory BP monitoring, blood examination, albumin‐creatinine ratio, carotid‐femoral pulse‐wave velocity assessment, and echocardiography for estimation of left ventricular mass index and diastolic function. Hypertensive men with ED (n=43, 24.7%) compared with those without ED were older (by 6.4 years, P <.05), had greater 24‐hour pulse pressure (by 4.3 mm Hg, P =.011) and a greater prevalence of nondipping status (72.2% vs 46.7%, P =.008), while the two groups did not differ in plasma glucose, lipid, creatinine, and albumin/creatinine ratio levels. Regarding cardiac adaptations, hypertensive men with ED exhibited only significantly lower tissue Doppler imaging–derived Em (by 1.6 cm/s, adjusted P =.035), while no difference in left ventricular mass index or pulse wave velocity were detected. ED in the setting of untreated newly diagnosed essential hypertension does not have an unfavorable impact on traditional markers of target organ damage. This finding suggests that ED assessment might not refine the traditional risk stratification procedure at least in the early stages of hypertensive disease.